2014
DOI: 10.1080/09658211.2014.985590
|View full text |Cite
|
Sign up to set email alerts
|

Recollection, not familiarity, decreases in healthy ageing: Converging evidence from four estimation methods

Abstract: Although it is generally accepted that aging is associated with recollection impairments, there is considerable disagreement surrounding how healthy aging influences familiarity-based recognition. One factor that might contribute to the mixed findings regarding age differences in familiarity is the estimation method used to quantify the two mnemonic processes. Here, this issue is examined by having a group of older adults (N = 39) between 40 and 81 years of age complete Remember/Know (RK), receiver operating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 74 publications
18
72
0
Order By: Relevance
“…It is also possible our M2 factor includes contributions of “non-criterial” recollection24 – i.e, memory for aspects of the Study episode in which an object was presented, other than the background with which it was paired (as required for our test of associative memory). According to dual-process theory, this would mean our M2 factor is a mixture of (non-criterial) recollection and familiarity, and if only the recollective component were affected by age, then this could reconcile our findings with a previous study arguing that age does not affect familiarity48. We therefore restrain from labelling our M2 factor as “familiarity”.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…It is also possible our M2 factor includes contributions of “non-criterial” recollection24 – i.e, memory for aspects of the Study episode in which an object was presented, other than the background with which it was paired (as required for our test of associative memory). According to dual-process theory, this would mean our M2 factor is a mixture of (non-criterial) recollection and familiarity, and if only the recollective component were affected by age, then this could reconcile our findings with a previous study arguing that age does not affect familiarity48. We therefore restrain from labelling our M2 factor as “familiarity”.…”
Section: Discussionsupporting
confidence: 45%
“…This is because our measure of item memory (recognition memory) is generally believed to be a function of both recollection and familiarity24. There are methods to separate the contributions of these two (e.g., fitting “dual-process” models to Receiver-Operating Curves, ROCs48), but unfortunately item memory was too close to ceiling for meaningful analysis of ROCs across our four levels of confidence. We did test a SEM version of an independent dual-process model (Table 1), in which item memory loaded on both a “recollection” factor (that also loaded on associative memory) and a “fluency” factor (that also loaded on priming), but this model was not preferred over our three-factor model.…”
Section: Discussionmentioning
confidence: 98%
“…Overall, these results clearly show that familiarity, in contrast to recollection, does not decline with age in healthy aging, as postulated by the dual-process models (Koen and Yonelinas, 2016;Prull et al, 2006;Yonelinas, 2002). They also provide cumulative evidence supporting a preservation of familiarity in healthy aging, considering the contradictory experimental data found in recent meta-analytic reviews (Koen and Yonelinas, 2014).…”
Section: Young (N ¼42)mentioning
confidence: 50%
“…Thus, in healthy aging, familiarity does not seem to be impaired in studies using Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/neuropsychologia ROC or PD methods, but it is impaired in studies that use the RK procedure (see the recent meta-analytic review by Koen and Yonelinas (2014); however, Koen and Yonelinas (2016), recently found converging evidence for a preservation of familiarity using the three procedures in a sample of older adults). With regard to familiarity in aMCI patients, results are even less consistent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation